An Updated Review on the Treatment Strategy for Spinal Metastasis from the Spine Surgeon’s Perspective - Hong, Seong Hwa; Chang, Bong-Soon; Kim, Hyoungmin; Kang, Dong-Ho; Chang, Sam Yeol (Asian spine journal, 2022)
Spinal metastasis is a common issue causing significant pain and disability in cancer patients. A multidisciplinary approach consisting of chemotherapy, radiotherapy, and surgical treatment is used for treating patients with metastatic spinal tumors. Due to recent advancements in medical and radiation oncology, like tumor genetics and stereotactic radiotherapy, this treatment strategy would change inevitably. Therefore, the decision-making systems developed for assisting physicians and surgeons to choose the most appropriate treatment for each patient with spinal metastasis need to evolve. In this review, the recent developments, validations, and modifications of these systems, as well as suggestions for future systems have been discussed. Recently, separation surgery combined with stereotactic radiotherapy (hybrid therapy) has gained popularity. Additionally, the evidence for hybrid therapy presented in the literature has been reviewed.